2022
DOI: 10.1177/11206721221143156
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography in Bietti crystalline dystrophy

Abstract: Purpose Bietti crystalline dystrophy (BCD) is a rare autosomal recessive retinal dystrophy caused by pathogenic variants of CYP4V2 gene and characterized by shiny yellow deposits in the retina and progressive atrophy of the retinal pigment epithelium (RPE) and choriocapillaris. The main aim of the present study is to describe the optical coherence tomography angiography (OCTA) characteristics of a patient affected by BCD. Methods A 59-years-old female with genetically confirmed BCD underwent an ophthalmologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, the severity of the vessel density reduction was similar across the different phenotypical manifestations, which ranged from mere RPE mottling up to large atrophic changes, suggesting that this peripapillary vascular impairment is independent of the stage of the disease. Even though the comparison of the OCTA findings described in other IRDs is hard due to the different pathogenesis of each subform, we have to underline that DCP is always involved, often also showing a correlation with BCVA [12][13][14][15][16][17][18][19][20][21]. Thus, DCP may represent an important biomarker to better characterize the stage of the disease and the extent of functional damage.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, the severity of the vessel density reduction was similar across the different phenotypical manifestations, which ranged from mere RPE mottling up to large atrophic changes, suggesting that this peripapillary vascular impairment is independent of the stage of the disease. Even though the comparison of the OCTA findings described in other IRDs is hard due to the different pathogenesis of each subform, we have to underline that DCP is always involved, often also showing a correlation with BCVA [12][13][14][15][16][17][18][19][20][21]. Thus, DCP may represent an important biomarker to better characterize the stage of the disease and the extent of functional damage.…”
Section: Discussionmentioning
confidence: 94%
“…Optical coherence tomography angiography (OCTA) has been used in several IRDs to characterize the vascular anatomy in the macula and to identify vascular patterns associated with a faster progression. In particular, a reduction in vessel density at the level of the deep capillary plexus (DCP) has been described in several IRDs, including Stargardt disease [12], cone dystrophies [13], Best vitelliform macular dystrophy [14], X-linked retinoschisis [15], choroideremia [16], occult macular dystrophy [17], congenital stationary night-blindness [18], retinitis pigmentosa [19,20], and Bietti crystalline dystrophy [21]. This study aimed to describe the OCTA features in eyes affected by CRB1-associated retinal dystrophies, as no prior study has explored the vascular alterations in these disorders.…”
Section: Introductionmentioning
confidence: 99%
“… 65 Consistently, a recent case report suggested that VD impairment of the retinal plexuses and CC ensued the primary RPE degeneration. 68 Miyata et al 66 analyzed 13 eyes of 13 patients with BCD using OCTA and showed a flow deficit in the choriocapillaris in 92% of their BCD patients. They also reported that subfoveal choriocapillaris thickness was correlated with visual acuity.…”
Section: Clinical Characteristics On Various Ancillary Testsmentioning
confidence: 99%